2D MOF Structure, Electrochemical Biosensing in Bioelectronic Applications - Yücer, Şeydanur; Saraç, Begüm; Çiftçi, Fatih (Nature, 2025)
Two-dimensional (2D) metal-organic frameworks (MOFs) have emerged as a groundbreaking class of materials with wide-ranging applications across biotechnology, bioelectronics, and tissue engineering. With their unique properties such as high surface area, tunable porosity, and flexibility in incorporating various metal ions, MOFs are instrumental in advancing the capabilities of bioelectronic sensors, tissue scaffolds, and biomedical imaging technologies. In biosensing, MOFs enable highly sensitive detection of biomolecules, including glucose, DNA, and proteins, by facilitating selective molecular interactions. This is particularly crucial for wearable technologies, where early detection of physiological changes is essential for timely diagnosis of diseases such as cancer and Alzheimer’s. MOFs’ adjustable porosity allows for selective adsorption of biomolecules, making them highly promising in biosensor development. Additionally, MOF-based sensors exhibit outstanding biocompatibility and mechanical strength, which are critical for seamless integration into wearable substrates. MOFs have also shown great potential in tissue engineering, where they enhance the functionality of scaffolds through their ability to load and release bioactive molecules. This controlled release mechanism is pivotal for promoting tissue regeneration, angiogenesis, and even drug delivery for cancer therapies. The versatility of MOFs in modulating physical properties such as mechanical strength, coupled with their capacity for functionalization, opens new avenues for creating bioactive scaffolds tailored to specific biomedical needs. In the realm of biomedical imaging, MOFs contribute significantly as contrast agents, particularly in magnetic resonance imaging (MRI) and computed tomography (CT). Their high surface area and tunable structure improve the precision and clarity of imaging, making them indispensable for enhancing diagnostic accuracy. MOFs also enable the development of multimodal imaging systems, combining diagnostic and therapeutic functionalities into a single platform. Furthermore, MOFs are being explored for their bioelectrochemical properties, where their integration into electrodes enhances the efficiency of biosensors and energy storage devices. The synergistic effects of MOFs with nanomaterials such as MXenes and carbon-based substances boost their electrocatalytic activity, which is crucial for applications in wearable sensors and bioelectronic systems. The future of MOF-based materials is promising, particularly as researchers focus on improving their biocompatibility, scalability, and operational stability. With further development, MOFs are expected to revolutionize the fields of bioelectronics, tissue engineering, and biomedical imaging, offering innovative solutions to some of the most pressing challenges in medical science.